Rationale for a new vehicle dynamic convention. (June 2021) - Williams, Dan; Margolis, Don
The term "slip angle" has been inconsistently applied in the vehicle dynamics field for some time, even in the presence of a clear definition in the SAE J670 standard defining vehicle dynamic terms. This work proposes the opposite of the Society of Automotive Engineers slip angle convention, not a completely unknown concept in the literature. This proposed slip angle convention is combined with a simple yet novel convention change for axle location. Differences between the conventional model and the new conventions are discussed, and the differences between the proposed convention and SAE J670 are clearly delineated. This work is intended as a reference to be used in the vehicle dynamics community by any researcher wishing to work with a model more intuitively pleasing and widely applicable than the accepted standard. This work does not present a particular new research result. Rather, it provides context on the often confusing choice of vehicle dynamic conventions and suggests a preferable selection.